2020
DOI: 10.1155/2020/3825629
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Screening for Acetylcholinesterase Inhibition and Antioxidant Activity of Quercus suber Cork and Corkback Extracts

Abstract: Purpose. Acetylcholinesterase (AChE) inhibitors are used to treat Alzheimer’s patients because they enhance cholinergic neurotransmission. It is urgent to find new and efficient inhibitors from natural sources, highly bioavailable with low or no toxicity. The plant kingdom is extremely rich in a variety of compounds that are potent AChE inhibitors: flavonoids and other phenolic compounds have been recognized as promising Alzheimer’s treatment agents. In this study, in vitro acetylcholinesterase inhibition, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
(56 reference statements)
0
15
1
Order By: Relevance
“…These results, together with the phenolic content values, demonstrate the high potential of these products as a source of high-value compounds. These results are promising since cork and grape (ethanol–water) extracts can be used as a source of potential natural antioxidants in nutraceutical applications or material surfacing protection …”
Section: Resultsmentioning
confidence: 99%
“…These results, together with the phenolic content values, demonstrate the high potential of these products as a source of high-value compounds. These results are promising since cork and grape (ethanol–water) extracts can be used as a source of potential natural antioxidants in nutraceutical applications or material surfacing protection …”
Section: Resultsmentioning
confidence: 99%
“…The serious side effects of synthetic inhibitors have forced the research community to search for natural alternatives. So far, galanthamine, huperzine A, and tacrine have been used for therapy [ 89 ]. Additionally, fruits and vegetables with proven target activities can be included in the daily menus of susceptible subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of Prunus persica L. water extracts to inhibit AChE effectively was also demonstrated in vivo [ 90 ]. Although it was thought that phenolic compounds are responsible for the inhibitory activity towards this enzyme [ 89 ], Rodríguez-Solana et al [ 91 ] reported a negative correlation (according to Pearson correlation coefficients) in carob liqueurs. Nakagawa et al [ 92 ] found no inhibitory activity of extracts of the peel and flesh of unripe fruits of “Akatsuki” and “Fastigiata” peach varieties.…”
Section: Resultsmentioning
confidence: 99%
“…Dihydroberberine and macelignan potently and effectively inhibited AChE with IC50 values of 1.18 and 4.16 µM, respectively [43]. Quercus suber cork and corkback ethanol-water extracts have been proven to be remarkable antioxidants with interesting AChE inhibitory activity [44]. Using the in vitro Ellman's technique, extracts, fractions, and compounds from Calceolaria talcana and Calceolaria integrifolia showed substantial inhibitory effects on AChE activity.…”
Section: Inhibition Of Acetylcholinesterase Activity Using Natural Co...mentioning
confidence: 99%